BIOACCUMULATION FACTORS OF MERCURY AT SOME SPECIAL MOLLUSCA IN NORTHEAST COASTAL AREA OF VIETNAM - Sinh, Le Xuan; Huyen, Nguyen Thu (Vietnam Journal of Marine Science and Technology, 2016)
Some organisms (snout otterclam Lutraria rhynchaena, granular ark Anadara granosa, corrugated lucine Austriella corrugata and lyrate Asiatic hard clam Meretrix lyrata) were chosen as subjects of this research because of their high bioaccumulation, their sedentary life and their filter feeding habit. Concentration of total mercury in the water was detected at 3 positions: Lan Ha bay - Cat Ba island, Hoang Tan commune - Quang Ninh province, Dong Bai commune - Hai Phong city. Result of this research showes the different levels of accumulation in tissues of 4 species but they are lower than MOH’s allowable value (0.5 micrograms/g). The bioaccumulation factors (BAF) of corrugated lucine Austriella corrugata, Granular ark Anadara granosa, Lyrate Asiatic hard clam Meretrix lyrata and Snout Otterclam Lutraria rhynchaena were 1.344, 344, 333 and 158 respectively. These factors show that accumulation total mercury in 4 species of mollusca is in natural tendency.